Analysis of the Influence of Halal Product, Brand Image, and Price on Purchase Decisions of MS Glow Skincare Products through Digital Marketing as a Moderating Variable - Khoiria Risky Tanjung; Zuhrinal M. Nawawi; Sri Sudiarti (Quantitative Economics and Management Studies, 2023)
This study aims to determine the extent of the influence of Halal Products, Brand Image, and Price through Digital Marketing as a moderating variable on the purchasing decision of MS Glow Skincare products among Muslim women in Medan City. The method used a quantitative approach. The sample consists of 100 women skincare product users in Medan City. Primary data collection instruments were used. The results of this study can be concluded as follows: the regression coefficient of the Halal Products variable of 0.469, indicating that an increase in the Halal Products variable will increase the decision of Muslim women in Medan city to use MS Glow skincare by 46%. The regression coefficient of Brand Image variable of 0.335, indicating that an increase in the Brand Image variable will increase the decision of Muslim women in Medan city to use MS Glow skincare products by 33%. The regression coefficient of the Price variable is 0.365, indicating that an increase in the Price variable will increase the decision of Muslim women in Medan city to use MS Glow skincare products by 36%. The variables of Halal Products, Brand Image, and Price collectively influence 42% of the decision of Muslim women in Medan city to use MS Glow skincare products. Digital Marketing, as a moderating variable, is able to strengthen the relationship by 59.7% between Halal Product, Brand Image, and Price on the Purchase Decision of MS Glow skincare products.